Old and new calcimimetics for treatment of secondary hyperparathyroidism: Impact on biochemical and relevant clinical outcomes - Pereira, L (2018)
Secondary hyperparathyroidism (SHPT) is associated with increased bone turnover, risk of fractures, vascular calcifications, and cardiovascular and all-cause mortality. The classical treatment for SHPT includes active vitamin D compounds and phosphate binders. However, achieving the optimal laboratory targets is often difficult because vitamin D sterols suppress parathyroid hormone (PTH) secretion, while also promoting calcium and phosphate intestinal absorption. Calcimimetics increase the sensitivity of the calcium-sensing receptor, so that even with lower levels of extracellular calcium a signal can still exist, leading to a decrease of the set-point for systemic calcium homeostasis. This enables a decrease in plasma PTH levels and, consequently, of calcium levels. Cinacalcet was the first calcimimetic to be approved for clinical use. More than 10 years since its approval, cinacalcet has been demonstrated to effectively reduce PTH and improve biochemical control of mineral and bone disorders in chronic kidney patients. Three randomized controlled trials have analysed the effects of treatment with cinacalcet on hard clinical outcomes such as vascular calcification, bone histology and cardiovascular mortality and morbidity. However, a final conclusion on the effect of cinacalcet on hard outcomes remains elusive. Etelcalcetide is a new second-generation calcimimetic with a pharmacokinetic profile that allows thrice-weekly dosing at the time of haemodialysis. It was recently approved in Europe, and is regarded as a second opportunity to improve outcomes by optimizing treatment for SHPT. In this review, we summarize the impact of cinacalcet with regard to biochemical and clinical outcomes. We also discuss the possible implications of the new calcimimetic etelcalcetide in the quest to improve outcomes.